Human papillomavirus infection in females with normal cervical cytology: Genotyping and phylogenetic analysis among women in Punjab, Pakistan. (January 2018) - Aziz, Hafsa; Iqbal, Huma; Mahmood, Humera; Fatima, Shazia; Faheem, Mohammad; Sattar, Areej Abdul; Tabassum, Sobia; Napper, Sanum; Batool, Syeda; Rasheed, Nuzhat
Abstract: Background: Globally, cervical cancer is the fourth most common cancer in women and the seventh most common cancer overall, accounting for an estimated 300 000 annual deaths. Human papillomavirus (HPV) is the second most common cause of cervical cancer worldwide. HPV screening is not a common practice in Pakistan. The aim of this study was to determine the prevalence of HPV and HPV types in women with a normal cytology of the cervix living in the upper and lower regions of Punjab, Pakistan, and to analyze the risk factors for HPV in this region. Methods: PCR analysis was performed for 1011 female patients with a normal cytology of the cervix from various districts of Punjab Province, Pakistan. Risk factors for the acquisition of HPV were studied. High-risk HPV types (HPV16 and HPV18) were detected using the Abbott Real Time HR HPV test. To determine the genotype, partial L1 region sequences of HPV-positive samples were subjected to sequencing using MY/09/MY11 primers, and a phylogenetic tree was constructed using CLC software. Results: The study found a 4.74% prevalence of HPV, with the most frequent HPV type found being the low-risk HPV6 (in 25% of infected individuals), followed by HPV55 (22.9%), HPV11 (20.8%), and high-risk types HPV45 (12.5%), HPV33 (8.33%), HPV18 (6.25%), and HPV16 (4.16%). Phylogenetic analysis of all HPV types in this study showed 80–99% nucleotide identity with types related to the same species. The sequences were clustered with China, India, Mexico, Iran, Slovenia, and Germany, showing the diversity in origin of the various genotypes prevalent in Pakistan. Conclusions: In this population with a normal cervical cytology, the prevalence of high-risk HPV types was very low. The major prevalent HPV genotype in Punjab Province of Pakistan was the low-risk HPV type 6, followed by HPV type 55. Sequencing of the partial L1 region suggested that the region was highly conserved in all reported sequences. This study highlights the need to conduct robust epidemiological studies in the region and to develop regular HPV screening so that the situation does not reach an alarming stage resulting in cervical cancer.